2015
DOI: 10.1039/c5dt02197a
|View full text |Cite
|
Sign up to set email alerts
|

Double [3 + 2]-dimerisation cascade synthesis of bis(triazolyl)bisphosphanes, a new scaffold for bidentate bisphosphanes

Abstract: A highly convergent synthesis of bis(triazolylphosphane oxides) was developed by a tandem copper-mediated Huisgen reaction-oxidative coupling. The phosphane oxides were reduced by trichlorosilane and the coordination of the resulting bisphosphanes was studied with various transition metals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 45 publications
1
29
0
Order By: Relevance
“…[21] As anticipated, the use of Bu 4 NI as additive remarkably increased the catalytic activity (entry 3, 91 % yield, 43 % ee). Similar poor results were obtained using LiI and LiBr (entries [13][14], whereas homoallylic alcohol 6a was obtained in good to excellent yields up to 96 % and good enantioselectivities up to 70 % using KI as additive (entries [15][16][17]. It was also found that the reaction could be performed in all solvents tested, the best catalytic activity in terms of yields and selectivities was obtained in propionitrile giving 6a in 95 % isolated yield with an encouraging optical purity up to 57 % (entry 10).…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…[21] As anticipated, the use of Bu 4 NI as additive remarkably increased the catalytic activity (entry 3, 91 % yield, 43 % ee). Similar poor results were obtained using LiI and LiBr (entries [13][14], whereas homoallylic alcohol 6a was obtained in good to excellent yields up to 96 % and good enantioselectivities up to 70 % using KI as additive (entries [15][16][17]. It was also found that the reaction could be performed in all solvents tested, the best catalytic activity in terms of yields and selectivities was obtained in propionitrile giving 6a in 95 % isolated yield with an encouraging optical purity up to 57 % (entry 10).…”
Section: Introductionsupporting
confidence: 78%
“…[14] Gratifying, it turned out that those ligands are effective Lewis bases for SiCl 4 -mediated enantioselective Abramov-type phosphonylation of aldehydes with trialkyl phosphites. Such derivatives were obtained through a tandem Cu-mediated Huisgen reaction-oxidative coupling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A signicant drop in the catalytic efficiency was observed with tributyl phosphite, while the bulky triisopropyl phosphite emerged as the best phosphonylating agent, yielding the desired diisopropyl a-hydroxyphosphonate 4d in an excellent isolated yield of 94% and a high enantiomeric ratio of 88.5/11.5 (entries [11][12]. In addition, we found that increasing (15 mol%) or lowering (5 mol%) the amount of catalyst 1 resulted in almost similar catalytic activities, although a longer reaction time (6 h) was required to reach completion with 5 mol% (entries [13][14]. Finally, we also examined a series of different additives including KI, NaI, I 2 but tetrabutylammoniun iodide proved to be the best choice for this transformation (entries 15-17).…”
mentioning
confidence: 67%
“…13 With these synthesized ligands we then envisioned that they could act as effective chiral Lewis bases for asymmetric catalysis. Indeed, achiral monotriazolyl phosphines also named clickphos showed high electron-donating behavior through N ⇨ P orbital overlap and we suspected that the bis-triazolyldiphosphines dioxides might exhibit a similar stabilization.…”
mentioning
confidence: 99%